Multi-slot based spectrum sensing with improved energy detector for cognitive radio network in presence of Rayleigh fading. (November 2016) - Bhowmick, Abhijit; Roy, Sanjay Dhar; Kundu, Sumit
Abstract: In this paper, the performance of multi-slot based spectrum sensing is investigated in a cooperative scenario where each cognitive radio (CR) user is equipped with an improved energy detector (IED). Two levels of fusion are employed: (i) sub-local decisions obtained in multiple mini slots are combined using OR logic fusion at a CR to obtain a local decision (ii) local decisions from CRs are combined using Majority logic fusion at FC to obtain final decision about the presence of PU. Both the sensing channel (S-channel) and reporting channel (R-channel) are assumed to be Rayleigh faded. Each CR sends its local decision over R-channel to FC after BPSK modulation. The performance of the cooperative spectrum sensing (CSS) using multi-slot and IED is assessed in terms of detection probability and false alarm probability. Furthermore, throughput of a CR is also evaluated under the proposed spectrum sensing scheme. Novel analytical expressions for the detection performance are developed. Performance of multi-slot based sensing is also compared with spectrum sensing without slotted sensing time. Impact of several sensing parameters such as sensing threshold, number of mini-slot, sensing channel SNR (SSNR), reporting channel SNR (RSNR) and IED parameters ( p ) on the detection performance of CR is indicated. The impact of multi-slot and IED parameter on throughput is also investigated.